Quantifying the flash effect and its dependence on average dose rate in vivo for 6 MeV electron and 6 MV photon beams - Paillas, Salomé; Taylor, Edward R.J.F.; Lövgren, Nathalie; Tullis, Iain D.C.; Petersson, Kristoffer (Clinical and translational radiation oncology, 2026)
•Increasing the average dose rate delays the onset, and reduces the severity, of radiation induced skin toxicity.•Similar FLASH effect following 6 MV photon and 6 MeV electron beam irradiation.•30 Gy/s shows a dose modifying factor (DMF) of ≈1.2–1.25, for both photon and electron beams.•DMF was increased to ≈1.5 for our highest used electron dose rates (≥1,800 Gy/s).•Radiotherapy is mainly delivered with MV photon beams, highlighting its importance as a future clinical modality for FLASH. This study shows that an increase in average dose rate delays the onset, and reduces the severity, of radiation induced skin toxicity in mice following hemi-thorax irradiation. The FLASH sparing effect’s magnitude and dependence on dose rate appear similar following irradiations using 6 MV photon and 6 MeV electron beams.